Abdominal and perineal scar endometriosis: Retrospective study on 40 cases. (September 2020) - Matalliotakis, Michail; Matalliotaki, Charoula; Zervou, Maria I.; Krithinakis, Konstantinos; Goulielmos, George N.; Kalogiannidis, Ioannis
Abstract: Objective(s): Abdominal and perineal scar endometriosis usually develop in association with a prior surgical scar. The purpose of the study was to detect and review patients' characteristics of these women over a long period. Study design: We retrospectively review the clinical records of 860 women with endometriosis between 1989 and 2019. Data were collected and analyzed from medical and pathological reports of 40 patients with abdominal and perineal scar endometriosis. Results: 26 patients (3, 0 %) were detected in the abdominal wall endometriosis group (AWE) (mean age 36, 5 ± 3, 4 years) and 14(1, 6 %) cases in the perineal endometriosis (PE) group (32, 5 ± 2, 4 years), respectively. We observed that 92, 3 % of women with AWE had undergone at least 1 cesarean section. Moreover, the majority of patients presented with abdominal pain (77, 0 %) and sensation of a mass (96, 2 %). 15, 4 % of cases had concurrent pelvic endometriosis and the recurrent rate of the disease was 15, 4 %. All cases with perineal scar endometriosis were multiparous and delivered vaginally with episiotomy. 92, 8 % of patients presented with cyclical pain and swelling. 3 cases suffered from perineal endometriosis combined with pelvic endometriosis. There was a recurrence of perineal endometriosis in 2 women (14, 2 %). Surgical excision was the standard treatment of this condition and tissue biopsy confirmed the diagnosis. Conclusions: Abdominal wall and perineal scar endometriosis are rare, multifactorial entities which are associated mainly with cesarean section and vaginal episiotomy. Clinicians should be aware of these conditions among all women of reproductive age presenting with cyclic or non-cyclic pain and swelling at the incision sites.